2016
DOI: 10.1136/bmjopen-2016-013088
|View full text |Cite
|
Sign up to set email alerts
|

Patient-controlled hospital admission for patients with severe mental disorders: study protocol for a nationwide prospective multicentre study

Abstract: IntroductionPatient-controlled hospital admission for individuals with severe mental disorders is a novel approach in mental healthcare. Patients can admit themselves to a hospital unit for a short stay without being assessed by a psychiatrist or contacting the emergency department. Previous studies assessing the outcomes of patient-controlled hospital admission found trends towards reduction in the use of coercive measures and length of hospital stay; however, these studies have methodological shortcomings an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…Previously, studies about self-referral admission programs have been reported from the United States (Nehls, 1994a, 1994b), Australia (Little & Stephens, 1999; Mortimer-Jones et al, 2016), Norway (Heskestad & Tytlandsvik, 2008; Moljord et al, 2016; Moljord et al, 2017; Rise et al, 2014; Sigrunarson, Moljord, Steinsbekk, Eriksen, & Morken, 2017; Tytlandsvik & Heskestad, 2009), the Netherlands (Helleman, Goossens, Kaasenbrood, & Achterberg, 2014; Koekkoek, van der Snoek, Oosterwijk, & van Meijel, 2010), Sweden (Strand, Bulik, von Hausswolff-Juhlin, & Gustafsson, 2017; Strand, Gustafsson, Bulik, & von Hausswolff-Juhlin, 2017), and Denmark (Ellegaard, Bliksted, Lomborg, & Mehlsen, 2017; Ellegaard, Mehlsen, Lomborg, & Bliksted, 2017; Thomsen et al, 2016). This indicates an international interest in new ways to organize mental health services and engage patients in self-management.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, studies about self-referral admission programs have been reported from the United States (Nehls, 1994a, 1994b), Australia (Little & Stephens, 1999; Mortimer-Jones et al, 2016), Norway (Heskestad & Tytlandsvik, 2008; Moljord et al, 2016; Moljord et al, 2017; Rise et al, 2014; Sigrunarson, Moljord, Steinsbekk, Eriksen, & Morken, 2017; Tytlandsvik & Heskestad, 2009), the Netherlands (Helleman, Goossens, Kaasenbrood, & Achterberg, 2014; Koekkoek, van der Snoek, Oosterwijk, & van Meijel, 2010), Sweden (Strand, Bulik, von Hausswolff-Juhlin, & Gustafsson, 2017; Strand, Gustafsson, Bulik, & von Hausswolff-Juhlin, 2017), and Denmark (Ellegaard, Bliksted, Lomborg, & Mehlsen, 2017; Ellegaard, Mehlsen, Lomborg, & Bliksted, 2017; Thomsen et al, 2016). This indicates an international interest in new ways to organize mental health services and engage patients in self-management.…”
Section: Introductionmentioning
confidence: 99%
“…Brukerstyring av innleggelser innen psykisk helsevern er et av flere virkemidler som kan vaere et alternativ til tvang, men der empiriske studier har hatt ulike resultater med forskjellige pasientgrupper: For pasienter med lidelser hovedsakelig innenfor bipolarog schizofrenispekteret har norske (Nyttingnes & Ruud, 2020;Sigrunarson et al, 2017), danske (Thomsen et al, 2016) og svenske (Skott et al, 2021) undersøkelser vist få fordeler i behandlingsresultater eller tjenestebruk fremfor vanlig henvisning og inntak.…”
unclassified